Creating non-fungible token (NFT)-backed emoji art from user conversations on blockchain - Maedeh Mosharraf; Mohammad Hossein Khorrami (Data Science and Management)
In the metaverse, digital assets are essential to define identity, shape the virtual environment, and facilitate economic transactions. This study introduces a novel feature to the metaverse by capturing a fundamental aspect of individuals–their conversations–and transforming them into digital assets. It utilizes natural language processing and machine learning methods to extract key sentences from user conversations and match them with emojis that reflect their sentiments. The selected sentence, which encapsulates the essence of the user’s statements, is then transformed into digital art through a generative visual model. This digital artwork is transformed into a non-fungible token, becoming a valuable digital asset within the blockchain ecosystem that is ideal for integration into metaverse applications. Our aim is to manage personality traits as digital assets to foster individual uniqueness, enrich user experiences, and facilitate more personalized services and interactions with both like-minded users and non-player characters, thereby enhancing the overall user journey.